2012
DOI: 10.1007/s10722-012-9808-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in wild and cultivated black raspberry (Rubus occidentalis L.) evaluated by simple sequence repeat markers

Abstract: Breeding progress in black raspberry (Rubus occidentalis L.) has been limited by a lack of genetic diversity in elite germplasm. Black raspberry cultivars have been noted for showing very few phenotypic differences and seedlings from crosses between cultivars for a lack of segregation for important traits. Despite these challenges, little molecular work has been done to explore genetic diversity and relationships in wild and cultivated black raspberry germplasm. Microsatellite, or simple sequence repeat (SSR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 26 publications
3
51
2
3
Order By: Relevance
“…However, in the light of other studies the possibility of hybridization between both species is rather small. Dossett et al (2012) found a very small number of hybrids in a broad sample of wild R. occidentalis germplasm. They noted little evidence of increased genetic differentiation in wild populations where both species co-occur (a few populations of R. occidentalis had "extra" alleles, but no definitive R. idaeus alleles were identified).…”
Section: Discussionmentioning
confidence: 98%
“…However, in the light of other studies the possibility of hybridization between both species is rather small. Dossett et al (2012) found a very small number of hybrids in a broad sample of wild R. occidentalis germplasm. They noted little evidence of increased genetic differentiation in wild populations where both species co-occur (a few populations of R. occidentalis had "extra" alleles, but no definitive R. idaeus alleles were identified).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, previous studies have analyzed the genetic diversity of boysenberry and blackberry using AFLP markers (Ipek et al 2009;Ryu et al 2014). While no sequence information is needed, the AFLP marker system is not as easy to perform as SSR markers, which show highly reproducible, co-dominant, multi-allelic, PCRbased, and medium throughput to assay (Dossett et al 2012;Stafne et al 2005). In particular, SSR markers developed for one plant species can be transferred between related species (Varshney et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Castillo et al (2010) also developed SSR markers from genomic libraries of red raspberry and blackberry. These SSR markers could be transferable across Rubus species and have been used to differentiate between wild and cultivated Andean blackberry (Rubus glaucus) (Marulanda et al 2012), to study genetic diversity in wild and cultivated black raspberry accessions (Dossett et al 2012), and to construct a genetic map of tetraploid blackberry (Castro et al 2013). However, there are no studies on the development or application of SSR markers in boysenberry.…”
Section: Introductionmentioning
confidence: 99%
“…Collection of plant materials has been previously described (Dossett and Finn 2010;Dossett et al 2012b). Briefly, during the summer of 2006, friends and colleagues living in eastern North America, within the native distribution of R. occidentalis, (USDA NRCS 2015) were solicited to send seed or fruit from wild plants in their area.…”
Section: Plant Materials and Field Maintenancementioning
confidence: 99%
“…For example, Dossett et al (2008) found significant improvements in vigor and disease resistance in progeny of a wild selection from North Carolina, NC 84-10-3, and Dossett and Finn (2010) found strong aphid resistance in wild germplasm from Maine, Michigan, and Ontario, Canada. Molecular studies have also shown that cultivated black raspberry may not be representative of the diversity found in wild germplasm (Dossett et al , 2012bWeber 2003). The primary objective of this study was to evaluate the performance of wild R. occidentalis germplasm collected from across the species' native range and planted in a common garden to gauge potential for use in breeding improved cultivars.…”
mentioning
confidence: 99%